Impact of alpha-amylase enzyme on the Rheological and Microstructural properties of the different types of rice flour doughs and bread - Dabash, Vikendra; Buresova, Iva (Emirates Journal of Food and Agriculture, 2022)
The purpose of this study is to discuss the significant role of the α-amylase enzyme in the production and rheological characteristics of gluten-free rice dough and baked bread. Small deformation and large deformation methods were used to evaluate the effect of the α-amylase enzyme addition on the dough and bread rheological characteristics. The baking properties of bread were evaluated by specific volume, baking loss, and Texture profile analysis parameters. The effect of the added enzyme on the dough microstructure was also evaluated. Small deformation study of doughs showed the highest significant changes after enzyme addition in 0.5S and extra-fine flour doughs. The dynamic rheological study of the flours doughs during the heating period showed significant changes in doughs properties as a function of α-amylase. After enzyme addition, a significant difference in crumb hardness was observed in the fine, semi-coarse, and extra-fine bread. After α-amylase addition in black rice, 0.5S and extra-fine doughs G’, G” and values were decreased. The research explains how the alpha-amylase enzyme effect the rheological characteristics of gluten-free dough and bread. Rheological analysis of doughs made from flour during the heating period indicated that the properties of the doughs were significantly affected by the presence of α-amylase.